Wie wird Weltliteratur gemacht? Globale Zirkulationen lateinamerikanischer Literaturen - Müller, Gesine (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2020)
The debate surrounding world literature has been brought into renewed focus in light of questions pertaining to global networks in a polycentric world. Beyond theoretical debates, however, there has been a marked lack of materialistic approaches that seek to shed light on processes underlying the formation of world literature. Using Latin American literature as an example, this volume shows how the global circulation of literature takes place.